Dampak Pemberian Jamur Jakaba dengan Dosis Berbeda dalam Budidaya Infusoria sp.: Study Tentang Kadar Nitrit, Nitrat, Dan Fosfat - Sri Mulyani; Melianti Tasik; Amal Aqmal; Indra Cahyono (Jurnal Perikanan Unram, 2024)
Seed quality and feed quality are major issues in fish and shrimp farming.  Infusoria is a natural microorganism as feed for fish and shrimp larvae, infusoria need a nutrient-rich environment to grow and develop. This study aims to determine the impact of giving Jakaba mushrooms with different doses on the content of important nutrients such as nitrites, nitrates, and phosphates in infusoria cultivation. This research will be carried out at the Integrated Fisheries Laboratory of Bosowa University in February 2024. This study used the quantitative experimental method Complete Randomized Design (RAL) with three treatments and three repeats. Infusoria sp with a density of 1.2 x 105 individuals / liter is maintained in a container with a volume of 1.5 liters filled with water used for fish maintenance. The process of making Jakaba mushrooms is by breeding the finished Jakaba mushrooms into leri water, then fermented for approximately fourteen days. The application of Jakaba mushroom fertilizer is carried out on the seventh day after the Infusoria culture is carried out according to the treatment dose, namely:: treatment A (15 ml/ liter); B (20 ml/ liter and C (25 ml/ liter). The results showed that giving Jakaba mushrooms with a dose of treatment C (25 ml / 1 liter) resulted in nitrite, nitrate levels of 0.334 ppm, 0.632 ppm and 0.334 ppm respectively.